Can, Want and Try: Parents' Viewpoints Regarding the Participation of Their Child with an Acquired Brain Injury - Thompson, M.; Elliott, Catherine; Willis, C.; Ward, R.; Falkmer, M.; Falkmer, T.; Gubbay, A.; Girdler, S. (Public Library of Science, 2016)
BACKGROUND: Acquired brain injury (ABI) is a leading cause of permanent disability, currently affecting 20,000 Australian children. Community participation is essential for childhood development and enjoyment, yet children with ABI can often experience barriers to participation. The factors which act as barriers and facilitators to community participation for children with an ABI are not well understood. AIM: To identify the viewpoints of parents of children with an ABI, regarding the barriers and facilitators most pertinent to community participation for their child. METHODS: Using Q-method, 41 parents of children with moderate/severe ABI sorted 37 statements regarding barriers and facilitators to community participation. Factor analysis identified three viewpoints. RESULTS: This study identified three distinct viewpoints, with the perceived ability to participate decreasing with a stepwise trend from parents who felt their child and family "can" participate in viewpoint one, to "want" in viewpoint two and "try" in viewpoint three. CONCLUSIONS: Findings indicated good participation outcomes for most children and families, however some families who were motivated to participate experienced significant barriers. The most significant facilitators included child motivation, supportive relationships from immediate family and friends, and supportive community attitudes. The lack of supportive relationships and attitudes was perceived as a fundamental barrier to community participation. SIGNIFICANCE: This research begins to address the paucity of information regarding those factors that impact upon the participation of children with an ABI in Australia. Findings have implications for therapists, service providers and community organisations.